Promoting blood vessel growth in ischemic diseases: challenges in translating preclinical potential into clinical success - Galina Dragneva; Petra Korpisalo; Seppo Ylä-Herttuala (The Company of Biologists, 2013)
Angiogenic therapy, which involves the use of an exogenous stimulus to promote blood vessel growth, is an attractive approach for the treatment of ischemic diseases. It has been shown in animal models that the stimulation of blood vessel growth leads to the growth of the whole vascular tree, improvement of ischemic tissue perfusion and improved muscle aerobic energy metabolism. However, very few positive results have been gained from Phase 2 and 3 clinical angiogenesis trials. Many reasons have been given for the failures of clinical trials, including poor transgene expression (in gene-therapy trials) and instability of the vessels induced by therapy. In this Review, we discuss the selection of preclinical models as one of the main reasons why clinical translation has been unsuccessful thus far. This issue has received little attention, but could have had dramatic implications on the expectations of clinical trials. We highlight crucial differences between human patients and animal models with regards to blood flow and pressure, as well as issues concerning the chronic nature of ischemic diseases in humans. We use these as examples to demonstrate why the results from preclinical trials might have overestimated the efficacy of angiogenic therapies developed to date. We also suggest ways in which currently available animal models of ischemic disease could be improved to better mimic human disease conditions, and offer advice on how to work with existing models to avoid overestimating the efficacy of new angiogenic therapies.